2002
DOI: 10.1046/j.1365-2141.2002.03717.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of dendritic cells in cancer patients treated with granulocyte colony‐stimulating factor and chemotherapy

Abstract: Summary. The number of dendritic cells (DC) circulating in the peripheral blood of cancer patients were monitored at multiple time points during chemotherapy and granulocyte colony-stimulating factor (G-CSF) support. DC were identified via the lack of expression of standard lineage markers and high expression of HLA-DR (LN -/DR + ). The expression of DC-associated markers, including CD83, CD11c, IL-3Ra (CDw123) and CD86, within this LN -/DR + population was also monitored. Maximal mobilization occurred during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
3
4
0
Order By: Relevance
“…This observation is consistent with recent studies that reported increases in the number of DCs during the restoration phase in the peripheral blood of cancer patients receiving combinatorial treatment with CTX and the growth factors G-CSF and GM-CSF (4244). Although it was not clear in these studies whether the increase in the frequency of DCs was due solely to the effects induced by CTX or by the growth factors, our results demonstrate that CTX is capable of inducing DC expansion in the peripheral blood in a murine model.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with recent studies that reported increases in the number of DCs during the restoration phase in the peripheral blood of cancer patients receiving combinatorial treatment with CTX and the growth factors G-CSF and GM-CSF (4244). Although it was not clear in these studies whether the increase in the frequency of DCs was due solely to the effects induced by CTX or by the growth factors, our results demonstrate that CTX is capable of inducing DC expansion in the peripheral blood in a murine model.…”
Section: Discussionsupporting
confidence: 93%
“…3). In line with our results, previous studies also showed increases in the numbers of DCs during the restoration phase in the peripheral blood of cancer patients receiving combinatorial treatment with CTX and G-CSF (3840). Although it was not clear in these studies whether the increase in the frequency of DCs was solely due to the effects induced by CTX or the growth factors, our results demonstrate that CTX per se is capable of inducing DC expansion in the peripheral blood in a murine model.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we tested this hypothesis recently using poly(I:C), the typical TLR3 agonist, to mature DCs and induce their migration to lymph nodes to enhance antigen-specific T cell responses (25). Our observation of post CTX DC expansion is consistent with the recent clinical studies that showed increases in the number of DCs in PBL of cancer patients treated with CTX and G-CSF (26, 27). Although these reports did not examine the sole effect of CTX or G-CSF on DC mobilization, the current results showed that CTX per se was capable of inducing systemic DC expansion.…”
Section: Discussionsupporting
confidence: 92%